2010
DOI: 10.1051/0004-6361/200913524
|View full text |Cite
|
Sign up to set email alerts
|

Weak lensing power spectra for precision cosmology

Abstract: It is usually assumed that the ellipticity power spectrum measured in weak lensing observations can be expressed as an integral over the underlying matter power spectrum. This is true at order O(Φ 2 ) in the gravitational potential. We extend the standard calculation, constructing all corrections to order O(Φ 4 ). There are four types of corrections: corrections to the lensing shear due to multipledeflections; corrections due to the fact that shape distortions probe the reduced shear γ/(1 − κ) rather than the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 53 publications
5
123
1
Order By: Relevance
“…This is the second order effect of the Born correction/lenslens coupling terms in the deflection angle (Krause & Hirata 2010). However, although this signal scales differently with l compared to the cosmic string signal considered here, it is below the level of this cosmic string signal on all scales and is unlikely to be detectable using currently planned radio surveys.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the second order effect of the Born correction/lenslens coupling terms in the deflection angle (Krause & Hirata 2010). However, although this signal scales differently with l compared to the cosmic string signal considered here, it is below the level of this cosmic string signal on all scales and is unlikely to be detectable using currently planned radio surveys.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, even on nonlinear scales in ΛCDM, the vector and tensor perturbations are negligible (Bruni et al 2014;Adamek et al 2014). At second order however, the scalar perturbations can generate rotation, through the term in the deflection angle that corresponds to the Born correction and lens-lens coupling (see Dodelson et al 2005;Krause & Hirata 2010;Thomas et al 2015). The size of this effect (and equivalently the size of the B-mode, see later) at second order in ΛCDM cosmologies has been examined in Krause & Hirata (2010) and Jain et al (2000) and found to be orders of magnitude smaller than the leading order signal.…”
Section: Rotation From Cosmological Perturbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid red curve shows the theoretical prediction by CAMB, in which we employed the revised Halofit for the nonlinear matter power spectrum. The orange curve shows the leading correction to the Born approximation (the so-called "post-Born correction") predicted by the third-order perturbation of the gravitational potential (Krause & Hirata 2010). We also plot downward pointing cyan arrows to indicate typical angular resolutions of CMB experiments: ℓ ∼ 400 (θ ∼ 30 arcmin) for BI-CEP, Keck, and LiteBIRD; ℓ ∼ 2000 (θ ∼ 5 arcmin) for Planck; ℓ ∼ 4000 (θ ∼ 3 arcmin) for POLARBEAR and CMB-S4; ℓ ∼ 10 4 (θ ∼ 1 arcmin) for SPT and ACT.…”
Section: Power Spectra Of Cmb Anisotropiesmentioning
confidence: 99%
“…Theoretical predictions for the shear correlation functions can be obtained from the matter power spectrum with relative ease (e.g. Bartelmann & Schneider 2001), but for the computation of the actually observable reduced shear correlation functions it is necessary to include higher-order corrections to the shear power spectrum (White 2005;Krause & Hirata 2010).…”
Section: Introductionmentioning
confidence: 99%